Analysis of Financial and Non Financial Factors to Revaluation of Fixed Asset - Ayu Surgawi, L; Solikhah, B (KnE Social Sciences, 2018)
This study aimed to examine the effect of Financial and Nonfinancial Factors to Fixed Asset Revaluation. Financial Factors consist of Leverage, Liquidity, Fixed Asset Intensity, Firm Size, and Firm Value. Nonfinancial Factors consist of Managerial Ownerships, Government Ownerships, and Independent Board of Commissioners. The population are 71 companies from Property, Real Estate, Building Construction, Infrastructure, Utility, and Transportation sector listed on the Indonesian Stock Exchange in 2014. Techique sampling using population sampling so obtained by 71 units analysis from annual report company’s sample in 2014. The analytical tool used descriptive statistic and logistic regretion. The result showed that Managerial Ownerships, and Government Ownerships have significantly positive effect on Fixed Asset revaluation. Leverage, Liquidity, Fixed Asset Intensity, Firm Size, Firm Value, and Independent Board of Commissioner have no effect on Fixed Asset Revaluation. The conclusions of this study is Non Financial Factors such as Managerial Ownerships, and Government Ownerships are more likely to revalue fixed assets. Keywords: Financial Factors; Nonfinancial Factors; Fixed Asset Revaluation